P-OGC58 Preoperative Enteral Feeding in Patients with Oesophagogastric Cancer. (16th December 2021) - White, Cathy; Arumugusamy, Mayilone; Robb, William
Abstract: Background: Patients with Oesophagogastric (OG) cancer undergoing multimodal treatment have a higher risk for progressive decline in their nutritional status. Our centre has seen increased numbers of patients using jejunostomy and gastrostomy tube feeding as an additional support during neoadjuvant chemotherapy and radiotherapy (nCRT). This audit aimed to evaluate the processes surrounding and the impact of this intervention. Methods: A retrospective review of 2019 medical records. Patients with OG cancer for treatment with curative intent that underwent an elective feeding tube insertion for preoperative supplementary feeding were included. Results: 14 patients were admitted for elective feeding tube insertion in 2019. On admission N = 10 patients (71%) had clinically severe weight loss (defined as ≥ 10% in 6 months, or ≥ 7.5% in 3 months or ≥ 5% in 1 month). Four (29%) had a dietetic assessment pre admission, with 1 patient (7%) trained on home enteral nutrition pre admission. Conclusions: This service is growing rapidly, patient numbers have more than doubled in 3 years. Enteral feeding is effective in preventing clinically significant weight loss in patients undergoing nCRT who progress to surgery. Short LOS: dietetic consult pre admission is essential to improve patient flow, education, preparation. Jejunostomy tube dislodged in 46% patients (n = 6), aim to improve strategies to avoid or best manage this. For future work: Examine effect on body composition (CT: sarcopenia) and examine patient's perspectives and quality of life.